Community empowerment? School autonomy, school boards and depoliticising governance - Gobby, Brad; Niesche, R. (SPRINGER, 2019)
© 2019, The Australian Association for Research in Education, Inc. The public education systems of many countries have undergone governance reforms involving administrative decentralisation, corporatisation and community ‘empowerment’. In this paper, we examine the significance of local participation and partnerships in the context of public school autonomy and their corporatisation. Focusing specifically on the use of school boards in the Independent Public Schools (IPS) initiative in Western Australia, we analyse the interview responses of five IPS principals using Foucauldian notions of governmentality, governance and community. The analysis shows that school boards are conceptualised and mobilised through the narrow technical–rationalist discourses of governance associated with corporatised school autonomy. School boards function as a new form of governmentality that constrains recruitment and participation in school decision-making in ways that depoliticise education. In response to the rise of school autonomy and corporatisation in Australia and elsewhere, we argue for wider local participation on school boards and local engagement with, rather than eschewal of, the politics surrounding education and the public good.